Exploring the potential of additive manufacturing for product design in a circular economy. (20th July 2019) - Sauerwein, Marita; Doubrovski, Eugeni; Balkenende, Ruud; Bakker, Conny
Abstract: Additive manufacturing, also known as 3D printing, is acknowledged for its potential to support sustainable design. In this paper, we explore whether the opportunities that additive manufacturing offers for sustainable design are also useful when designing for a circular economy, and to what extent additive manufacturing can support design for a circular economy. We performed a literature review on the sustainability aspects of additive manufacturing and held a series of interviews with designers about their 3D printed design projects to obtain in-depth information. The interviews were analysed using annotated portfolios, a novel analysis method created specifically for this research. This resulted in a visual representation of the outcomes. We found that additive manufacturing supports circular design strategies by creating opportunities to extend a product's lifespan, for instance by enabling repair or upgrades, even if these products were not originally designed for ease of repair or upgrading. However, the use of monolithic structurally complex parts that support design for recyclability may hinder high value product recovery, like repair. Besides this, the current offer of 3D printable materials should be extended with materials developed for durable use, as well as high-value reuse. Concluding, when accounting for these drawbacks, additive manufacturing is able to support multiple product life cycles and can provide valuable contributions to a circular economy. Highlights: Additive manufacturing creates opportunities for applying circular design strategies. Sustainable additive manufacturing opportunities should support multiple product lifecycles. Availability of sustainable materials for additive manufacturing is an issue. The interview data were analysed with annotated portfolios, a newly developed method.